Analisis Pengaruh Faktor Modal Kerja terhadap Kinerja Proyek Konstruksi Gedung di Kota Jambi - Salman Alparisi Agusjaya; Nasfryzal Carlo; Zulherman Zulherman (Universitas Batanghari Jambi, 2023)
Jambi City Government continues to strive to increase the amount of construction infrastructure that is beneficial to the people of Jambi City. This study aims to identify the factors that influence working capital and analyze the dominant factors that influence working capital. Research through literature review, research questionnaires, population and sample as well as data analysis stages which include data analysis. The first objective of the research is to carry out validity tests, test reliability, normality test, KMO and Bartlett's test and data analysis. The objective of the two studies is to carry out the Mean analysis test to see the dominant factor. Based on the results of the study, it shows that: Factor VII/ Performance, Factor II/ Cash and management policies, Factor VI/ Level of working capital requirements, Factor IV/Receivables and Inventories, Factor V/ Receipts and expenses, Factor 1/ Project Costs, Factor VIII/ Advances and Payments, Factor III, Working capital management. The factor that has the most influence on the contractor's working capital on the performance of building construction projects in Jambi City is Factor VII/Performance with a score of 3.80. While Factor 1/Project Costs got a score of 3.06, Factor VIII/Down Payment and Payments got a score of 3.03, and Factor III/Working capital management got the lowest score, namely 2.99. The Importance of Contractor Performance Factors on Working Capital, efforts to improve contractor performance in building construction projects, as well as collaborative strategies to improve working capital management.